Nigeria : Publication of Financial Sector Assessment Program Documentation -- Technical Note on Crisis Management and Crisis Preparedness Frameworks. (IMF Staff Country Reports; Country Report ;, 2013)
The Nigerian financial system underwent a banking crisis in 2008-09, owing to the global financial crisis and domestic events. The decisive crisis response effectively stabilized the banking system, but the challenge now is to devise a credible exit strategy. The Central Bank of Nigeria (CBN) has a broad resolution toolkit, which was put to use during the crisis to resolve the intervened banks. The Nigerian authorities set up the Asset Management Corporation of Nigeria (AMCON) to purchase nonperforming loans of banks.